Konflik Batin Tokoh Iyan Dalam Novel Iyan Bukan Anak Tengah Karya Armaraher: Kajian Psikologi Sastra Sigmund Freud - Rachmah Ega Pramesti; Hespi Septiana (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the forms of inner conflict, the maturation process, and the manifestations of the id, ego, and superego personality structures of the character Iyan in Armaraher's novel "Iyan Bukan Anak Tengah." A literary psychology approach was used, utilizing Sigmund Freud's psychoanalytic theory. The method employed was descriptive qualitative research. The research data consisted of words, phrases, sentences, and dialogues that demonstrate the inner conflict, maturation process, and personality structure of the main character. Data collection techniques included intensive reading, documentation, recording, and data classification. Data analysis was conducted using descriptive-analytical techniques. The results indicate that Iyan's inner conflict consists of four forms: conflict resulting from lack of affection, social and environmental pressure, defense mechanisms, and emotional trauma. These conflicts serve as drivers for the character's maturation process through emotional control, obedience, forgiveness, social adaptation, and acceptance of reality. The manifestations of the personality structure show that the id dominates at the beginning of the story through the need for affection and attention. The ego functions to adapt to reality, while the superego develops through moral awareness, ultimately shaping the character's psychological maturity. This research demonstrates that inner conflict plays a crucial role in the formation of a character's identity and personality development.